B-CELL EPITOPE PREDICTION of Mycobacterium tuberculosis Ag85A ANTIGEN - Ika Puspita Dewi (UNEJ e-Proceeding)
Tuberculosis (TB) infection is one of the majorpublic health problems in developing countryincluding Indonesia. The endemic of TB infectioncaused by Mycobacterium tuberculosis becameworse because of the multidrug-resistant TB (MDRTB).M. tuberculosis had special feature which isits cell wall or envelope that consists of complexlipids, lipoglycans and peptidoglycans (Forrelad,2013). The cell wall consisted of two layers, theinner and the outer. The inner consisted ofpeptidoglycan sacculus veiled bymycolylarabinogalactan polysaccharide layer. Theouter envelope consisted of trehalose 6,6′-dimycolate (TDM; cord factor) which wassynthesized by fibronectin binding protein (fbp)/antigen 85 (Ag85) complex (Elamin, 2011).The Ag85 complex was a 30–32 kDa proteinconsisting of three proteins (Ag85A, Ag85B, andAg85C). It had several functions, includingenzymatic mycolyl-transferase activity for couplingof mycolic acids to cell wall arabinogalactan, cordfactor biogenesis (trehalose-dimycolate), and hadcapacity to bind to fibronectin and elastin of theextracellular matrix proteins (Huygen, 2014). Thisprotein were encoded by three paralogous geneslocated in different regions of the bacterialgenome (D’Souza, 2003). The Ag85 complex wasthe major secreted protein of M. tuberculosis cellculture besides of its association with bacterialsurface. It had essential role in the pathogenesis oftuberculosis. The ability of this protein to bindfibronectin promoted M. tuberculosis adhesion tothe mucosal surface, thus facilitating the bacteriato entry into the host cell. However, the main roleof it to the virulence of M. tuberculosis was theability to synthesis of cell wall lipids (Forrelad,2013).Ag85A (fbpA) was part of the antigen 85 complex.It had several functions including as thetriacylglycerol synthase and might have the keyrole in stability of cell wall and storage compoundsbiosynthetic for the survival of M. tuberculosisduring the dormant state (Elamin, 2011). Belisle etal. (1997) studied the role of Fpb proteins in thevirulence of mycobacteria using M. tuberculosisH37Rv fbpA mutant and suggest that the Ag85A(fbpA) would be essential in the virulence of M.tuberculosis. The study by Elamin et al (2011) hadthe same result that Ag85A might be the key playerfor formation of lipid storage bodies and thus alsoessential for the establishment and maintenanceof a persistent tuberculosis infection.Ag85A and Ag85B are among the most promisingtuberculosis vaccine candidates because theirability to induces T-cell response and production ofIFN-γ (Huygen, 2014). The T-cells epitopes of theAg85A have been identified. (Ivanyi, 2014). The Bcellepitope of Ag85A have rarely investigated.Thus, this study is aimed to predict the B-cellepitope of Ag85A. The result of this study will beuseful for investigation of the immunogenicity andantigenicity of Ag85A antigen.